2014
DOI: 10.1177/0954411914527741
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional geometric analysis of the talus for designing talar prosthetics

Abstract: Proper understanding of the complex geometric shape of the talus bone is important for the design of generic talar body prosthetics and restoration of the proper ankle joint function after surgery. To date, all talus implants have been patient-specific with the limitation that complex computer modeling is required to produce a mirrored image from the unaffected opposite side followed by machining a patient-specific prosthesis. To develop an "off-the-shelf" non-custom talar prosthesis, it is important to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…More specifically, our findings revealed that changes in PC1 can result in up to 81% of points in the male talus and 84% of points in the female talus to deviate more than 1 mm. Thus, PC1 can be considered as a scale amongst tali; its role as a major contributor has been confirmed and widely made use of in previous studies (Islam et al, 2014 ; Trovato et al, 2017 ; Zhao et al, 2019 ). In contrast, as the second major contributor, PC2 leads to a lower percentage of deviations greater than 1 mm: 55% of the deviations for male tali and 36% for female tali ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…More specifically, our findings revealed that changes in PC1 can result in up to 81% of points in the male talus and 84% of points in the female talus to deviate more than 1 mm. Thus, PC1 can be considered as a scale amongst tali; its role as a major contributor has been confirmed and widely made use of in previous studies (Islam et al, 2014 ; Trovato et al, 2017 ; Zhao et al, 2019 ). In contrast, as the second major contributor, PC2 leads to a lower percentage of deviations greater than 1 mm: 55% of the deviations for male tali and 36% for female tali ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 77%
“…Earlier studies have investigated the morphology of the talus by either using anatomical landmarks to capture the characteristics of the talus (Mahato, 2011 ), or by performing 3D deviation analysis in a software (Islam et al, 2014 ). Not only would these methods involve extensive manual work, but would also be prone to errors and inconsistencies (Stagni et al, 2004 , 2005 ; Hayes et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires a generalization of the geometry of the talus. Islam et al 15 proposed an implant in five sizes; however, that study had limitations including a small sample size (n = 27), lack of a diverse sample selection such that the female population was severely underrepresented, a randomly selected reference implant, and an incremental jump in size of volume (which will be more significant in the smaller sizes as volume is a cubic function). Trovato et al 8 improved upon this study by increasing the sample size (n = 91) with 45% of the subjects being female, selectively choosing the reference implant, and using incremental jump in the cube root of the volume between sizes.…”
Section: Introductionmentioning
confidence: 99%